Longitudinal studies with continuous responses. - Laird,NM; Donnelly,C; Ware,JH (Stat Methods Med Res, 1992)
The analysis of serial measurements obtained in longitudinal studies plays an increasingly prominent role in applied research. The last few years have seen the development of many new techniques for carrying out analyses, including computer software. These methods can be used in a variety of standard problems, including repeated measures and cross-over designs, as well as growth curve analyses. We review these new methods, their application, and available computer packages. Data from a longitudinal study of lung function is used to illustrate the methods.